Productivity Performance in The Manufacture Sector of Cameroon : How Does Family and non-Family Firm Perform - Atemnkeng, Johannes Tabi; Tambi, Mbu Daniel (Journal of Entrepreneurship, Management and Industry (JEMI), 2018)
This research provides insights on factors affecting performance of family firms in comparison with the non-family firms making use of data from Cameroon. We estimated total factor productivity via a Cobb–Douglas production function while accounting for the correlation between input levels and productivity. As concerns the management and control of firms, family members are heavily involved in family firms than those of non-family firms which are mostly managed externally. It is observed that non family firms employ more labour and invests more in capital compared to family owned and managed firms. Based on the two-staged least-squares technique, results show that family firms and even those managed by families are, on average less productive than externally managed family firms and non-family owned firms after controlling for sector as well as other characteristics.  The findings are important for both policy makers and practitioners.